Measuring satisfaction with user requirement related building performance attributes: a questionnaire - Seshadhri, Gopikrishnan; Paul, Virendra Kumar (Penerbit Universiti Kebangsaan Malaysia, 2018)
User satisfaction should be the primary concern of the infrastructure development agencies, especially in residential projects. Government residential projects are built with huge expenditure and maintenance of these assets also consumes enormous public funds. The facility maintenance agency remains accountable for the expenditure incurred on these assets to ensure performance. Presently public spending by government agencies lacks effective monitoring post construction especially on maintenance of assets. It makes the government agencies less accountable on their expenditure as also with the procedures/processes followed for maintenance of these assets. There is a need to put an effective system in place to firstly gauge and secondly monitor the performance of all such government assets. Mere expenditure of allotted funds by the end of a financial year cannot be a viable indicator to vouch for the genuineness of spending. The most ideal route to measure its effectiveness is the most important stake holder, viz. the end user. This paper is a part of an ongoing research where the ultimate overarching goal is to develop a conceptual framework to implement an intervention strategy for gauging and enhancing user satisfaction based on user requirement related building performance attributes. This paper deals with development of an instrument necessary to garner feedback on user satisfaction. The content of the questionnaire is based on carefully selected attributes for user requirements that reflect building performance. 84% of an expert group comprising of architects, planners, engineers, facility managers and academia agreed with the grouping and selection of attributes and 73% of them agreed with the need to amplify the attributes in the form of sub attributes for better comprehension of participants. Content, translational and construct validity of the questionnaire developed based on these attributes/sub attributes was also carried out establishing the veracity of the instrument. User satisfaction surveys conducted based on this survey instrument shall enable implementation of effective intervention strategies by FM agencies and also be a measure to establish their efficacy and accountability.